Keputusan Masyarakat Menggunakan Kredit Pemilikan Rumah (KPR) Menggunakan Akad Murabahah di Kota Tebing Tinggi - M. Maulana Malik Nasution; Putri Nazli (Jurnal Nuansa : Publikasi Ilmu Manajemen dan Ekonomi Syariah, 2025)
This study aims to analyze the factors influencing people's decisions to use a Home Ownership Credit (KPR) with a murabahah contract at a sharia bank in Tebing Tinggi City. The research method used is a descriptive qualitative approach, with data collection techniques through observation, in depth interviews, and documentation of people who have used the murabahah KPR product. Informants were selected purposively to obtain relevant and in depth data. The results show that people's decisions are influenced by several main factors, including compliance with sharia principles, price transparency, certainty of fixed installments, ease of financing processes, promotions conducted by the bank, housing location, and the brand image of the sharia bank. The murabahah contract is considered to provide clarity of profit margins from the start and stability of installment payments throughout the financing period, thereby increasing public security and trust. These findings indicate that consistent application of sharia principles and appropriate marketing strategies play a significant role in increasing public interest in sharia housing financing products.